Penerapan Model Teaching Personal and Social Responsibility (TPSR) untuk Meningkatkan Kemandirian Siswa di SMP - Kusnaedi, Kusnaedi; Kusnaedi, Prilya Nur Salsabila; Hidayat, Yusuf; Carsiwan, Carsiwan (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2024)
Character development and student independence are major challenges in junior high school education, especially in this increasingly complex era. This study examines the effectiveness of the implementation of the Teaching Personal and Social Responsibility (TPSR) model in improving students' independent behavior at SMPN 29 Bandung. Using a Classroom Action Research (CAR) design, this study involved 100 students who were observed during three learning cycles. Data collection was conducted through a combination of structured questionnaires and systematic observations. The results of the analysis showed a significant increase in students' independence scores from 76.69 to 89.85, reflecting the success of the TPSR intervention. This model has been proven effective in developing various aspects of independence, including decision-making, interpersonal skills, and personal and social responsibility. More importantly, this study revealed that students were able to transfer the skills learned into the context of everyday life outside of school. These findings provide strong empirical evidence to support the implementation of the TPSR model as a pedagogical strategy in developing student independence. It is recommended that schools adopt and implement the TPSR model systematically and sustainably to maximize its positive impact on students' character development.